Progres de L'a,e dans La Vie Spirituelle - Faber, Frederic, William (Victor Retaux, Libraire-Editeur, 1905)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃